Challenges in Understanding and Transacting Contemporary EVS Textbooks - SHARMA, KAVITA (THE PRIMARY TEACHER, 2015)
Understanding that young children perceive their surroundings holistically and to reduce the curriculum load for them, the National Curriculum Framework (NCF) 2005 based on the National Policy on Education 1986, recommends Environmental Studies to be taught as an integration of Science, Social Science and Environmental Education at the primary stage. It exists as a separate curricular area from Classes III to V. However, at Classes I and II the related concerns are addressed through language and mathematics. The textbooks developed on this depart from the traditional approach and demand considerable changes from teacher-centric to learner-centered teaching-learning giving primacy to children’s voices and their past experiences and mould/devise the strategies based on their responses. The approach has been accepted and implemented by most of the states and UTs across the country. Many of them have adopted/ adapted the NCERT textbooks in Environmental Studies based on NCF–2005. In order to understand the gaps and challenges in transaction of these books, field visit to a government school in New Delhi was undertaken for a period of three months. To understand the gaps between intention and transaction of EVS, observations of teachers teaching EVS were made and the author (who was part of the curriculum development of EVS) herself taught some lessons. The article, based on this field visit experience, compares the transaction of EVS by a qualified and trained teacher to that of the author to understand the gaps in development/transaction of EVS curriculum in order to come up with the strategies to bridge them appropriately